Antibacterial Activities and Synergistic Interaction of Citrus Essential Oils and Limonene with Gentamicin against Clinically Isolated Methicillin-Resistant Staphylococcus aureus - Apichai Sreepian; Supaluk Popruk; Daranee Nutalai; Chayanit Phutthanu; Preeyaporn M. Sreepian (The Scientific World Journal)
Citrus reticulata Blanco and Citrus aurantifolia are the edible plants which contain several biological properties including antibacterial activity. The aims of the present study were to determine the chemical compositions and evaluate antibacterial activities of citrus essential oils extracted from the fruit peels of C. reticulata (CREO) and C. aurantifolia (CAEO), alone and in combination with gentamicin, against a panel of clinically isolated methicillin-resistant S. aureus (MRSA) (n = 40) and methicillin-susceptible S. aureus (MSSA) (n = 45). Gas chromatography-mass spectrometry analysis revealed that 12 and 25 compounds were identified in CREO and CAEO with the most predominant compound of limonene (62.9–72.5%). The antibacterial activities were determined by agar disk diffusion and resazurin-based microdilution methods. The results found that almost all MRSA isolates were resistant to ciprofloxacin, erythromycin, and clindamycin, and some isolates were resistant to gentamicin. CREO and CAEO exhibited inhibitory effects toward clinical isolates (MIC: 1.0–32.0 and 8.0–32.0 mg/mL, respectively), with a similar trend to limonene (MIC: 1.0–32.0 mg/mL). However, the higher antibacterial effects were found in CREO and limonene when compared to CAEO (p < 0.01). In combination effect, the results showed the synergistic interaction of gentamicin with CREO and limonene on the MRSA and MSSA isolates (FIC indexes: 0.012–0.258 and 0.012–0.375), but that interaction of gentamicin with CAEO was observed only on MRSA (FIC index: 0.012–0.016). These findings demonstrated the potential of these citrus essential oils as natural antibacterial agents that may contribute to reduce the emerging of antimicrobial-resistant bacteria.